Xp11.2 Translocation Renal Cell Carcinoma With TFE3 Rearrangement: Distinct Morphological Features and Prognosis With Different Fusion Partners - Ge, Yan; Lin, Xingtao; Zhang, Qingling; Lin, Danyi; Luo, Luqiao; Wang, Huiling; Li, Zhi (Frontiers in Oncology, 2021)
Background Renal cell carcinoma (RCC) associated with Xp11.2 translocation/TFE3 gene fusion is a rare and new subtype of RCC and was classified by the WHO in 2004. Since then, multiple 5′ fusion partners for TFE3 have been reported; however, the impact of individual fusion variant on specific clinicopathologic features of Xp11.2 RCCs has not been well defined. Methods Four Xp11.2 translocation RCCs were identified by morphological, immunostaining, and fluorescence in situ hybridization (FISH) assays from 200 patients who attended Guangdong General Hospital between January 2017 and January 2020. All these four cases were further analyzed by RNA sequencing to explore their TFE3 gene fusion partners. The clinicopathologic features, including clinical manifestations, pathological findings, treatment strategies, clinical outcomes, and follow-up information on Xp11.2 translocation RCCs, were recorded and evaluated. Results These four cases affected one male and three females. The median age was 13 years at the time of diagnosis (range = 4–20 years). All the examined tumors were unilateral and unifocal. The largest diameter of these tumors ranged from 2.0 to 10.0 cm, and the average was 5.55 cm. Regional lymph node or distant metastasis developed in two patients. Three cases demonstrated known fusions: ASPCR1–TFE3 (two cases) and PRCC–TFE3 (one case). However, one case showed an unreported VCP–TFE3 fusion gene in Xp11.2 translocation RCCs. Immunohistochemistry results revealed tumor cells diffusely positive for TFE3, but have no consistency in other markers. Moreover, there were different clinical prognoses among the different variant TFE3 rearrangements; RCC patients with VCP–TFE3 translocation had worse prognosis compared to those with other fusion types. Follow-up were available for all the patients and ranged from 3 to 36 months. Three patients were without evidence of disease progression, while that with VCP–TFE3 fusion died of the disease 3 months after the diagnosis. Conclusion In conclusion, our data expand the list of TFE3 gene fusion partners and the clinicopathologic features of Xp11.2 RCCs with specific TFE3 gene fusions. We identified a novel VCP–TFE3 fusion in Xp11.2 translocation RCCs for the first time, which has unique morphology and worse prognosis than those with other variant TFE3 rearrangements. Integration of morphological, immunohistochemical, and molecular methods is often necessary for the precise diagnosis and optimal clinical management of malignant tumors.